Quantifying the influence of mutation detection on tumour subclonal reconstruction - Lydia Y. Liu (Nature Portfolio, 2020)
The impact of variant calling algorithms on the analysis of intra-tumour heterogeneity has not been properly quantified. Here the authors measure the variability of 22 pipelines with different variant callers and clustering algorithms for subclonal reconstruction to inform future analyses.